Development of Viral Vectors Based on Citrus leaf blotch virus to Express Foreign Proteins or Analyze Gene Function in Citrus Plants - Agüero, Jesús; Ruiz-Ruiz, Susana; Vives, María C.; Velázquez, Karelia; Navarro, Luis; Pena, Leandro; Moreno, Pedro; Guerri, José (2017)
Viral vectors have been used to express foreign proteins in plants or to silence endogenous genes. This methodology could be appropriate for citrus plants that have long juvenile periods and adult plants that are difficult to transform. We developed viral vectors based on Citrus leaf blotch virus (CLBV) by duplicating a minimum promoter (92 bp) either at the 3′ untranslated region (clbv3′pr vector) or at the intergenic region between the movement and coat protein (CP) genes (clbvINpr vector). The duplicated fragment (–42/+50) around the transcription start site of the CP subgenomic RNA (sgRNA) had the full promoter activity and induced synthesis of a new sgRNA in infected plants. Agroinoculation with these vectors resulted in systemic infection of Nicotiana benthamiana and the resulting virions systemically infected citrus plants. A clbvINpr vector carrying the green fluorescent protein (GFP) gene expressed GFP in citrus plants and triggered gfp silencing in gfp-transgenic citrus plants, and vectors carrying fragments of the phytoene desaturase or the magnesium chelatase genes incited a silencing phenotype in citrus plants. These silenced phenotypes persisted in successive flushes. Because CLBV infections are symptomless in most citrus species, the effective silencing induced by CLBV-derived vectors will be helpful to analyze citrus gene function.